Analisis Arsitektur Perilaku terhadap Tingkat Kenyamanan Pasien Kanker di Rumah Singgah Surabaya - Nabilah, Amelia; Utomo, Heru Prasetiyo (Universitas Medan Area, 2025)
A halfway house is a temporary residence that functions as a place for treatment or to wait for the scheduled queue for treatment at RSUD Dr. Soetomo. Considering the large number of patients referred to the hospital, the role of halfway houses is very important, especially for underprivileged residents. The biggest problem that patients in halfway houses face is feeling lazy about seeking treatment so they don't have a sense of optimism about getting better. The desire to recover can be achieved if the patient's environmental conditions are very supportive in the process of creating feelings of calm, eliminating stress, positive perceptions, and developing a sense of enthusiasm in carrying out treatment. Therefore, in-depth research is needed to explore and understand how the application of behavioral architecture principles can influence the comfort level of patients in Surabaya halfway houses. From the results of the study, it was found that the shelter in Surabaya had implemented the principles of behavioral architecture, the design and layout of the space in this building had taken into account ergonomics or the condition of cancer patients. The spatial planning factors, size and shape, furniture, color, sound, temperature and lighting in this building are in accordance with its function. However, it is still not friendly for wheelchair users. Even so, the patient's condition is maintained because he feels comfortable and can speed up the healing process.